The effect of target foreknowledge on visual search for categorically separable orientation targets. - Hodsoll, J; Humphreys, G (2005)
This research note assesses the role of target foreknowledge in visual search for categorically defined orientation targets, as first described by Wolfe et al. [Wolfe, J. M., Friedman-Hill, S. R., Stewart, M. I., and O'Connell, K. M. (1992). The role of categorisation in visual search for orientation. Journal of Experimental Psychology: Human Perception and Performance, 18, 34-49]. We compared search with known versus unknown (respond to the odd item) targets. An RT advantage for categorical search only emerged with known targets. The evidence points to an important role for top-down processes in search for categorically--defined orientation targets.